(untitled) (TAJ: Journal of Teachers Association, 2022)
Introduction: The reduction and fixation of femoral neck fractures within 12 hours is considered optimal. However, studies have reported insufficient fracture reduction, rather than surgical fixing time, is a predictor of complication. In our country, patients attend tertiary care facilities late, ranging from days to even weeks; hence 12 hours principle is frequently violated. The present study assessed the outcomes of surgically treated femoral neck fracture with cannulated cancellous hip screws within two weeks of the injury. Methods: This prospective study observed 19 patients with traumatic intracapsular femoral neck fracture aged between 18 to 60 years and injury to surgery time up to 2 weeks. For the fixation of the neck, three standard cannulated screws (7.3mm cancellous) were inserted according to the "3 Point Principle". Data regarding demographic variables, baseline variables of fracture personality, and outcomes variables were recorded. The final outcome was sassed according to Harris Hip Score. The relation between the duration of fixation and the final outcome was analyzed. Result: 19 patients with femoral neck fractures were included in the study. The mean age of the 19 patients was 36.58 ±11.93 years, with 16 (84.21%) of them from the male gender. The minimum duration from injury to operation time was 2 days, and the maximum duration was 13 days. Among 19 patients mean duration was 6.58 days with SD =±2.99 days. 73.6% of the cases had the surgery within 7 days of sustaining the injury. According to Harris Hip Score, 17(89.60%) of the cases had a satisfactory outcome. The relationship of final outcome with injury to operation time was not statistically significant (p = 0.421). This means there was no difference in Harris Hip Score between operations done early or late. Conclusion: The time interval from injury to surgery did not influence the functional outcome. Cannulated screw fixation is a viable option in treating femoral neck fracture. TAJ 2021; 34: No-2: 122-128